Pelatihan Pembuatan Media Pembelajaran bagi Guru Kelas Menggunakan Aplikasi Canva - Mutiara Dana Elita; Moefty Mahendra; I Made Ratih Rosanawati; Geby Adellestia; Kevin Fanreza Ardiansyah; Fikrun Najih Hidayat (Educate: Journal of Community Service in Education, 2025)
The implementation of learning that utilizes interactive technology-based learning media is a form of technological development in the world of education. This can help teachers in implementing fun learning. So the role of learning media is becoming increasingly important. Thus, teachers are required to hone their abilities in creating interactive learning media. The creation of learning media can utilize applications. This can be proof that technology can be an intermediary in delivering learning so that learning objectives are maximized. This community service aims to train teachers to create interactive learning media. Thus, learning activities can carry out learning activities more interestingly. This activity is carried out for 1 week. The Community Service Program uses the Participatory Learning and Action (PLA) method. The PLA method is implemented through three stages of activity, namely socialization, discussion, and practice so that it can increase the involvement of community service participants actively. The results of this community service increase teacher creativity in creating learning media. After the training, teachers became aware that teachers can use all the features on the Canva application for free if accessed with aku belajar.id. The conclusion of this community service is that the Canva application has proven to be a potential tool for improving the quality of learning, as long as it is supported by good resource management in the school environment